(untitled) (Biological Sciences - PJSIR, 2002)
The separation of closely boiling organic acid is discussed using dissociation extraction techniques. A mathematical model is developed to calculate the separation factor in dissociation extraction process sho,ving good agreement with experimental data. Important system variables are the concentration of the solutes, ratios of solutes in the organic phase and the solvent used . Experimental data is presented to show the affect of these parameters on the extraction of cresols.